Association between outdoor artificial light at night, circadian health, and LDL-C in intracranial artery atherosclerotic stenosis - Le Yang; Quan Wang; He Zheng; Yiqing Wang; Zhigang Miao; Hao Li; Yi Yang (Clinical Epigenetics)
Abstract Background Outdoor artificial light at night (ALAN) exposure interferes with sleep–wake cycles, leading to sleep disorders, and disrupts metabolic processes, which are closely interconnected. Disruptions in circadian rhythms caused by ALAN may indirectly contribute to metabolic dysregulation, especially in vulnerable populations such as patients with intracranial artery atherosclerotic stenosis (ICAS). This study aimed to evaluate the relationship between outdoor ALAN exposure and low-density lipoprotein cholesterol (LDL-C) control in ICAS patients, and to investigate the underlying mechanisms. Methods We investigated the relationship between outdoor ALAN exposure and LDL-C control in ICAS patients, estimating residential ALAN levels using satellite images. Sleep quality was assessed using validated questionnaires, and generalized additive models were applied to examine the association between ALAN and LDL-C control. Mechanistic insights were explored through animal-based untargeted metabolomics and DNA methylation analyses. Results A total of 1010 ICAS patients were included, of whom 32 were classified as having poor LDL-C control after three months of management. We found a significant association between outdoor ALAN intensity and poorer LDL-C (control odds ratio = 1.02, 95% CI 1.00, 1.05 per 1 nW/cm−2/sr−1 increase). Sensitivity analyses verified the stability of this association. Metabolic profiling reveals ALAN may regulate lipid metabolism by affecting ATP-binding cassette (ABC) transporter proteins. Additionally, dim ALAN treatment promoted global hypomethylation in mice, while melatonin treatment partially counteracted these effects without reducing the stress response. Conclusion Increasing ALAN intensity surrounding residences was associated with poorer LDL-C control in ICAS patients, potentially mediated by circadian rhythm disruptions, global methylation levels, and ABC transporter protein expression. These findings suggest that managing urban outdoor lighting could serve as a potential strategy to reduce the public health burden of cerebrovascular and metabolic diseases.